Microscopic morphology and elemental composition of atmospheric particles from seven micro-environments in Xi'an. Issue 9 (November 2019) - Yan, Lu; Cheng, Yan; Wu, Feng; Chang, Hong; Liu, Song; Wang, Ye Lin; Yu, Chuck Wah; Zhang, Yun Wei
This paper characterizes the morphological and elemental compositions of individual particles in seven micro-environments of Xi'an. Atmospheric particulate matter samples were collected at one suburban site (Duling Park (DL)), three urban sites (roadside site (RS), clear days (CD), dusty days (DD)) and three indoor sites (hot pot (HP), barbecue (BBQ), hospital (HO)) during March–April in 2017. A total of 469 particles were analysed by a scanning electron microscopy with an energy dispersive X-ray spectroscopy. Seven types of particles were observed, including sulphate particles, iron oxide particles, dust mineral particles, soot, organic aerosols, silicon–aluminium (Si–Al)-rich fly ash and biological particles. Soot accounted for 22% in BBQ, indicating an effect of BBQ coal burning. Sulphate particles were found in high abundance (14–15%) in HP and HO samples, consistent with the occurrence of secondary chemical reactions. Organic aerosols accounted for 13% in HO, 20% in HP and BBQ samples due to cooking of food and human factors. Comparison of samples in indoor and outdoor environments showed that the external transmission of dust mineral particles and Fe oxide particles played a key role in indoor levels. The microscopic analysis also demonstrated that the particles in Xi'an were highly distributed with fine particles (less than 3 µm) and that the morphology of fine particles tended to be spherical.